A DUF4148 family protein produced inside RAW264.7 cells is a critical Burkholderia pseudomallei virulence factor. Issue 1 (1st January 2020) - Welkos, Susan; Blanco, Irma; Okaro, Udoka; Chua, Jennifer; DeShazer, David
ABSTRACT: Burkholderia pseudomallei: is the etiological agent of the disease melioidosis and is a Tier 1 select agent. It survives and replicates inside phagocytic cells by escaping from the endocytic vacuole, replicating in the cytosol, spreading to other cells via actin polymerization and promoting the fusion of infected and uninfected host cells to form multinucleated giant cells. In this study, we utilized a proteomics approach to identify bacterial proteins produced inside RAW264.7 murine macrophages and host proteins produced in response to B. pseudomallei infection. Cells infected with B. pseudomallei strain K96243 were lysed and the lysate proteins digested and analyzed using nanoflow reversed-phase liquid chromatography and tandem mass spectrometry. Approximately 160 bacterial proteins were identified in the infected macrophages, including BimA, TssA, TssB, Hcp1 and TssM. Several previously uncharacterized B. pseudomallei proteins were also identified, including BPSS1996 and BPSL2748. Mutations were constructed in the genes encoding these novel proteins and their relative virulence was assessed in BALB/c mice. The 50% lethal dose for the BPSS1996 mutant was approximately 55-fold higher than that of the wild type, suggesting that BPSS1996 is required for full virulence. Sera from B. pseudomallei -infected animals reacted with BPSS1996 and it was found to localize to the bacterial surface using indirect immunofluorescence. Finally, we identified 274 host proteins that were exclusively present or absent in infected RAW264.7 cells, including chemokines and cytokines involved in controlling the initial stages of infection.